The teacher perception of the role of the intrapersonal factors in the improvement of their pedagogical practices (Praxis Educativa, 2021)
This article presents the results of a study aimed at describing the relationships between intrapersonal factors and the improvement of pedagogical practices in teachers in the Metropolitan Region of Chile, mainly due to the scarce information about this relationship in the academic literature. It corresponds to a study with a qualitative approach, based on the theoretical-methodological guidelines of Grounded Theory, which was carried out by conducting six interviews with teachers with outstanding performance in the classroom. The results derived from the open and axial coding are presented, which give a preliminary account of the teachers’ perception of how modifications are produced in their pedagogical practices and how this change is related to the intrapersonal factors of the teachers. The results highlight the role of personal traits and the belief system as central categories that intervene in the change of pedagogical practices, discussing the importance of advancing in models that contribute from a systemic and complex approach in the understanding of the person and the pedagogical practices.